2005
DOI: 10.1167/iovs.05-0781
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Measurement of Rodent Intraocular Pressure with a Rebound Tonometer

Abstract: The rebound tonometer was easy to use and accurately measured IOP in rats and mice. This technique, together with advances in genetic and other biological studies in rodents, will be valuable in the further understanding of the etiology and pathology of glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
173
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(190 citation statements)
references
References 23 publications
11
173
1
2
Order By: Relevance
“…Additional ligations of ≥1 presumably patent episcleral veins were performed at 24 h, and at 1 or 2 weeks following the initial surgery, if IOP was not elevated at 24 h or did not remain elevated at weekly measurement intervals, or if newly formed episcleral veins became evident. Of note, in this study and in our previous studies employing this same model [9][10][11], very few mice required additional ligation surgery at 24 h or 2 weeks after the initial ligation; rather, in most mice, new veins that became apparent by 1 week were ligated, even if IOP had not fallen below levels measured at 24 h. As described previously by us and others [9][10][11][12], IOP determinations were made between 10.00 am and 2.00 pm in both eyes prior to, and at weekly intervals following, IOP elevation using the TonoLab Rebound Tonometer system (Colonial Medical Supply, Franconia, NH, USA).…”
Section: Experimental Glaucoma Modelsupporting
confidence: 76%
“…Additional ligations of ≥1 presumably patent episcleral veins were performed at 24 h, and at 1 or 2 weeks following the initial surgery, if IOP was not elevated at 24 h or did not remain elevated at weekly measurement intervals, or if newly formed episcleral veins became evident. Of note, in this study and in our previous studies employing this same model [9][10][11], very few mice required additional ligation surgery at 24 h or 2 weeks after the initial ligation; rather, in most mice, new veins that became apparent by 1 week were ligated, even if IOP had not fallen below levels measured at 24 h. As described previously by us and others [9][10][11][12], IOP determinations were made between 10.00 am and 2.00 pm in both eyes prior to, and at weekly intervals following, IOP elevation using the TonoLab Rebound Tonometer system (Colonial Medical Supply, Franconia, NH, USA).…”
Section: Experimental Glaucoma Modelsupporting
confidence: 76%
“…Savinova et al, 11 Danias et al, 14 and Wang et al 15 all determined the IOP of C57BL/ 6J mice under xylazine/ketamine sedation followed by IOP measurements either by cannulation alone or by simultaneous cannulation and rebound tonometry. The data reported by these groups for the normal IOP in C57BL/6 mice (IOP IN ¼ 13.1 mmHg, 5 IOP R ¼ 9.2 and 9.8 mmHg 14,15 ) suggest that rebound tonometry in mice in vivo may underestimate the IOP.…”
Section: Discussionmentioning
confidence: 93%
“…16 The rebound tonometer used in this study is a relatively new device based on similar physical principles as the vibration tonometer. 22,23 Reports of rebound tonometer use in rats, 15,24 mice, 14,15,25 and human patients 26,27 demonstrated that this type of tonometer is convenient to use and yields reliable data.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, rebound tonometer was used because it is portable, has a lower platinum, and its impact on the eye is fast and minimal. In addition, previous studies reported that measurement of IOP with this instrument was well tolerated in other species, being quick and inducing minimal stress (WANG et al, 2005). The choice of handheld tonometer used in this study was because it was available in the routine of study group, it has already been validated for horses and it does not require anesthetic drops or constant calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment intraocular pressure is crucial parameter for a complete ophthalmic exam as it contributes to the diagnosis of ocular diseases. Several methods have been described for measuring IOP in animals, including applanation, indentation, and rebound tonometry (GUM et al, 1998;KNOLLINGER et al, 2005;WANG et al, 2005 RUSANEM et al, 2010;PEREIRA et al, 2011;PIGATTO et al, 2011). In animals, both applanation and rebound tonometry are used, and correlation has been revealed between these methods (KNOLLINGER et al, 2005).…”
Section: Introductionmentioning
confidence: 99%